The effectiveness of biology learning in the materials of the respiration system based on integrated multimedia character education at SMAN 2 Percut sSi Tuan T.P 2021/2022 - Simanjuntak, Lasroin; Sidabutar, Hudson (ARKA INSTITUTE, 2022)
This study aims to determine the effectiveness of learning biology on the respiratory system material based on integrated multimedia character education at SMAN 2 Percut Sei Tuan TP 2021/2022. The sample used in this study was one class (40 people). This research is quantitative descriptive. The instruments used to collect data are multiple choice tests and questionnaires. The data collection method used in this study was observation, interviews, questionnaires and tests (multiple choice) as a result of student learning given a score. The percentage of students' learning completeness (80%) or 24 students are said to be complete because they get a score that exceeds the KKM limit and (20%) or 6 students are not complete because the student is not able to get a score above the KKM limit. Thus, it can be concluded that learning biology on the material of the multimedia-based respiratory system integrated character education at SMAN 2 Percut Sei Tuan TP 2021/2022 is quite effective.